Upaya Penanganan Limbah Olahan Ikan Menjadi Pakan Ternak Unggas dan Pupuk Organik Cair - Komariyati, Komariyati; Padmarsari, W.; Surachman, Surachman (Jurnal Pengabdi, 2018)
Fish processed waste is an environmental problem for fish processing business in Kuala Secapah village, Mempawah Regency, West Kalimantan. This activity is an integration between the handling of fish processing waste into poultry feed and liquid organic fertilizer and efforts to improve nutrition and income of fish processors and marketers. Implementation of activities includes several stages: socialization, training, mentoring and monitoring evaluation. The indicator of the success of the activity can be seen from (1) the high entrepreneurial spirit for the fish processing and marketing group, (2) increased sales turnover through the management of production systems. The long-term goal of this activity is to become a model of eco friendly fish processing business and become a model of community development for related institutions.